PELATIHAN EKONOMI SYARIAH BAGI KOPERASI DAN USAHA MIKRO KECIL MENENGAH (UMKM) DI KOTA LHOKSEUMAWE - Aryati . (Universitas Negeri Medan, 2016)
Abstract : Training For Islamic Economic Cooperation And Micro Small Medium (Smes) In Kota Lhokseumawe. Community service aims to improve the knowledge, insight, and understanding of the nature and basic economic concepts of sharia, Islamic economic financing products and how its application. This activity uses lectures, question and answer, discussion, presentations and mentoring. Based on the evaluation, the results achieved are: (1) capable of increasing the knowledge and understanding of the managers of cooperatives and SMEs about the nature and basic economic concepts of sharia; (2) the growing awareness of participants about the importance of applying the basic principles of operating in accordance with Islamic economic perspective; (3) has clarified financing products sharia economic and operational mechanism as well as sharing distribution by sharia; (4) the growing partnership between the participants based on the principles of Islamic economics. Keywords : Islamic Economics, Cooperative, Micro business Abstrak : Pelatihan Ekonomi Syariah Bagi Koperasi Dan Usaha Mikro Kecil Menengah (UMKM) Di Kota Lhokseumawe. Pengabdian masyarakat ini bertujuan untuk meningkatkan pengetahuan, wawasan, dan pemahaman mengenai hakikat dan konsep dasar ekonomi syariah, produk pembiayaan ekonomi syariah serta cara penerapannya. Kegiatan ini menggunakan metode ceramah, tanya jawab, diskusi, presentasi serta pendampingan. Berdasarkan evaluasi, hasil yang dicapai adalah: (1) mampu meningkatkan pengetahuan, dan pemahaman para pengurus koperasi dan UMKM tentang hakikat dan konsep dasar ekonomi syariah; (2) tumbuhnya kesadaran peserta tentang pentingnya menerapkan prinsip dasar operasional sesuai dengan perspektif ekonomi Islam; (3) telah memperjelas produk-produk pembiayaan ekonomi syariah dan mekanisme operasional serta distribusi bagi hasil secara syariah; (4) tumbuhnya kemitraan antara para peserta yang berlandaskan pada prinsip ekonomi Islam. Kata Kunci: Ekonomi Syariah, Koperasi, Usaha Mikro